Next-generation OPAC - Abu Hanipah, Rabiahtul Adauwiyah; Mansor, Yushiana (IIUM Press, 2011)
This chapter introduces the concept of next-generation Online Catalogue (OPAC) and its salient features. It illustrates how the Web 2.0 technologies have enhanced the performance of traditional OPAC. Among features incorporated are faceted browsing, relevance ranking, spell-checking and keyword suggestion, and tagging.